Speech Acts on Women's Double Standards in Barbie's Monologue (2023) - Gunawan, Ake Putri; Prihandini, Asih (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
This research aims to examine the speech act on Gloria Vaughn's monologue utterances from the 2023 Barbie film, concentrating on the distribution of expressive, assertive, directive, and commissive utterances. The analysis aims to carefully examine the verbal techniques employed in Gloria's speech, elucidating its emotional impact, advocacy for change, and cultural importance. Descriptive, statistical and interpretative methods were used to examine the data in accordance with J.L. Austin's speech act theory. The results demonstrate that 31.58% of Gloria's monologue consists of expressive utterances, 26.32% of assertive utterances, 26.32% of directive utterances, and 15.79% of commissive utterances. These figures highlight the emotional impact, call for change, and individual dedication intertwined within Gloria's persuasive speech. The analysis underscores the educational, artistic, and societal import of deconstructing Gloria's speech acts, accentuating its function as an instructive implement, a refraction instigator, and a potent artistic and emotive medium. The analysis results provide a more profound comprehension of the intricacies of womanhood and the resonant significance conveyed in Gloria's monologue. These insights are vital for academics, learners, and individuals engaging with societal challenges and self-recognition. Keywords: Pragmatics, Speech Acts, Utterance, Barbie 2023